GROWTH AND FIBER MORPHOLOGY OF ABACA (Musa textilis Nee) RATOONS AS INFLUENCED BY PLANT DENSITY AND NITROGEN LEVEL - Gloria, Nestor M. (Annals of Tropical Research, 1985)
An old abaca plantation was subjected to butcher harvest as a rejuvenation process. The subsequent ratoons were evaluated in terms of growth and fiber dimensions as influenced by plant density and nitrogen level. Replants served as checks in determining the merits of ratooning. Ratoons emerged approximately 13 days earlier, had more rapid growth and higher dry matter yield of stalk and leaves than the replants. These horticultural characteristics were not significantly affected by plant density and nitrogen fertilizer application after a 12-month period. Leaf N content significantly increased with increased N fertilizer application during the sixth month but not after 12 months. It was not influenced by plant density. Fiber cellular dimensions were not affected by the application of 0, 50, 100 and 200 kg N/ha as well as by plant density. However, fiber dimensions of ratoons at any density were bigger than those of replants.